Upaya Meningkatkan Hasil Belajar Pendidikan Pancasila dan Kewarganegaraan Melalui Model Pembelajaran Kontekstual Pada Siswa Kelas XI TKRO SMK Negeri 3 Semarang Tahun Pelajaran 2018-2019 - Sutrisno Sutrisno (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
This class action research aims to find out if the use of contextual learning models can improve PKn learning outcomes in grade XI students of TKRO SMK Negeri 3 Semarang Year 2018/2019. This research was conducted at SMK Negeri 3 Semarang. This type of research is qualitative by using a class action research approach. The main data is obtained from informants such as principals, and teachers. Data collection methods with observations, in-depth interviews, and documentation methods. The results showed that (1) The increase in student learning outcomes was achieved by an increase in average grades from the initial data of 72.07 increased to 76.38 in the first cycle and increased again to 80.34 in the second cycle. The completeness of 41.38% increased to 62.86% in the first cycle and reached 93.10% in the second cycle; (2) The increase in student learning activities from the initial data of 41.38% of students active in learning increased to 63.79% in the first cycle and increased again in the second cycle to 88.79%.Keywords: contextual model, learning outcomes, activities, PPKn